Pemahaman Materi Fiqih Melalui Kajian Kitab Fathul Qorib di Pondok Pesantren Mahir Arryadl Ringinagung Kediri - Hidayah, Ridho; Sajdah, Meilisa (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Learning the book Fathul Qorib is a way of delivering fiqh material in learning. So that the students can understand and conclude problems regarding religious jurisprudence material such as procedures for purification, prayer procedures, tayamum, caring for corpses and others. This article is a case study with a qualitative approach, the results of this research are an understanding of fiqh material through a study of the book Fathul Qorib. In the process of understanding the science of fiqh, fiqh teachers use the bandongan, takror and practice methods. The bandongan method is a method in which there is an ustadz who reads, translates and explains the contents of the yellow book, then the students listen, interpret and listen to the ustadz's reading. The takror method is a discussion method that discusses Fiqh in depth and solves actual problems based on ibarot from the yellow book which is carried out in Islamic boarding schools. The takror method is carried out by providing opportunities to ask questions according to the fasl discussed in the study of the Fathul Qorib book. Based on the results of activities to understand fiqh through studying the book of Fathul Qarib at the Mahir Arryadl Islamic boarding school, it can be concluded that students can increase their knowledge and understanding of fiqh material through studying Fathul Qorib, and can apply it in everyday life.